Water Filter
The water purification filter, utilizing fibrous activated carbon and a biodegradable polyester resin binder with specific melting point characteristics, addresses the issues of low filtration flow rate and poor handling in existing filters, achieving effective chlorine filtration and improved handling for pot-type water purifiers.
Patent Information
- Application Number
- JP2020147398
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-09-02
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2040-09-02
AI Technical Summary
Existing water purification filters using activated carbon and biodegradable binders have low filtration flow rates, making them unsuitable for pot-type water purifiers, and they often suffer from poor handling and mechanical strength.
A water purification filter is developed using fibrous activated carbon and a biodegradable polyester resin as a binder, where the activated carbon is fused together by the resin. The biodegradable polyester resin has a melting point of 80-140°C and is used as a sheath in core sheath-type composite fibers, ensuring a high filtration flow rate and improved handling.
The filter maintains a certain free residual chlorine filtration capacity while achieving a practically unproblematic filtration flow rate for pot-type water purifiers, with high hardness and excellent handling properties.
Smart Images

Figure 0007664597000002 
Figure 0007664597000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a water purification filter. [Background technology]
[0002] 2. Description of the Related Art Conventionally, water purification filters using activated carbon have been used to purify tap water, for example by removing free residual chlorine, and various water purification filters have been developed.
[0003] Known water purification filters include activated carbon, which is a filtering material, and a binder component for binding the activated carbon together.
[0004] After use, such water purification filters are discarded as household waste and are incinerated, landfilled, etc. From the viewpoint of protecting the global environment, it is required to reduce the energy required for incineration or to improve the biodegradability of the filters when they are landfilled.
[0005] One method for improving the biodegradability of a water purification filter is, for example, to make the binder component biodegradable. As a water purification filter having a biodegradable binder component, for example, a fluid purification material containing an aluminosilicate and a binder thereof, in the form of a porous block or sheet, in which the binder is a biodegradable polymer, is known (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2004-504126 Summary of the Invention [Problem to be solved by the invention]
[0007] However, the purification material disclosed in Patent Document 1 is obtained by compressing and molding granular charcoal, etc., and has a low filtration flow rate. Therefore, when used as a filter for a pot-type (pitcher-type) water purifier in which raw water stored in a storage section is allowed to fall by its own weight and pass through a filter for purification, there was a problem that it took a long time to filter.
[0008] Here, the present inventors conceived of making the activated carbon filter medium and the biodegradable binder component fibrous and bulky (low density) in order to increase the filtration flow rate of the purification material disclosed in Patent Document 1. However, the present inventors' investigations revealed that simply making the activated carbon filter medium and the biodegradable binder component fibrous would not increase the filtration flow rate while maintaining a certain free residual chlorine filtration capacity, and that the filter hardness would be low, resulting in poor handling.
[0009] Therefore, the present invention aims to solve the above problems and provide a water purification filter that contains activated carbon as a filter medium and a biodegradable polymer as a binder component, with activated carbon particles fused together by the biodegradable polymer, which maintains a certain level of free residual chlorine filtration capacity, has a filtration flow rate that is practically acceptable even when used as a pot-type water purifier, and has a certain degree of hardness and is easy to handle. [Means for solving the problem]
[0010] The present inventors have studied the above problem and found that, for example, when the biodegradable binder component is a fully melted fibrous binder made of a single biodegradable polyester resin, the biodegradable polyester resin itself has a relatively low fluidity when thermally melted, so in order to sufficiently bond the activated carbons together, the biodegradable polyester resin must be melted by heat treatment at a temperature close to the melting point of the biodegradable polyester resin. At this time, the entire fibrous binder is easily thermally deformed by the heat treatment, and for example, the fibrous binder may be crushed into a film. The present inventors have found that this causes fewer voids in the water purification filter, and the resulting water purification filter may have poor filtration flow rate.
[0011] Therefore, the present inventors conceived that the problem could be solved by including a biodegradable polyester resin as the sheath of a core-sheath composite fiber as a fibrous binder, and setting the difference between the melting point of the synthetic resin included as the core of the core-sheath composite fiber and the melting point of the biodegradable polyester resin (melting point of the synthetic resin included as the core - biodegradable polyester resin included as the sheath) to 20°C or more. However, even in the above case, the filter may become brittle, or the core of the core-sheath composite fiber may become flattened due to thermal deformation during heat treatment during adhesion. When the present inventors investigated the cause of this, they found that biodegradable polyester resin has a relatively small fluidity when melted by heat, and that the adhesion between activated carbons tends to be relatively insufficient compared to other polyesters, and that the biodegradable polyester resin itself is relatively hard and brittle, so that the resulting water purification filter may have poor mechanical strength and poor handleability. In addition, they found that if the heat treatment temperature during bonding is increased in order to increase the fluidity of the biodegradable polyester resin, which is the binder component disposed in the sheath portion, when it is thermally melted, the core portion of the core-sheath type composite fiber becomes more susceptible to thermal deformation, which in turn reduces the voids in the water purification filter, and the resulting water purification filter may have poor filtration flow rate.
[0012] Therefore, the present inventors conducted extensive research and found that by making the difference between the melting point of the synthetic resin contained as the core of the sheath-core composite fiber and the melting point of the biodegradable polyester resin (melting point of the synthetic resin contained as the core - melting point of the biodegradable polyester resin) 20°C or more and making the biodegradable polyester resin used as the sheath of the sheath-core composite fiber have a melting point of 80 to 140°C, it is possible to ensure a relatively low melting point that is easy to heat treat during bonding and appropriate fluidity when melted, and to suppress thermal deformation of the core of the sheath-core composite fiber.
[0013] In addition, the activated carbon is in the form of fiber, and the specific surface area of the filter is 500 to 1,800 m 2 / g, filter density 0.12~0.30g / cm 3 The inventors have found that by making the water purification filter by winding a nonwoven fabric sheet containing the fibrous activated carbon and a core-sheath type composite fiber having the biodegradable polyester resin as a sheath portion, while maintaining a certain level of free residual chlorine filtration capacity, it is possible to provide a water purification filter that has a filtration flow rate suitable for a pot-type water purifier, has a certain degree of hardness, and is easy to handle.
[0014] That is, the present invention provides the following aspects. Item 1. A water purification filter comprising activated carbon and a biodegradable polyester resin, the activated carbon being fused together by the biodegradable polyester resin, the activated carbon being in the form of a fiber, the biodegradable polyester resin having a melting point of 80 to 140°C and contained as a sheath of a core-sheath type composite fiber, the difference between the melting point of the synthetic resin contained as the core of the core-sheath type composite fiber and the melting point of the biodegradable polyester resin (the melting point of the synthetic resin contained as the core - the melting point of the biodegradable polyester resin) being 20°C or more, the water purification filter being formed by winding a nonwoven fabric sheet containing the fibrous activated carbon and the core-sheath type composite fiber, and the density of the water purification filter being 0.12 to 0.30 g / cm 3 The specific surface area of the water purification filter is 500 to 1800 m 2 / g water purification filter. Item 2. The water purification filter according to Item 1, wherein the biodegradable polyester resin is an aliphatic polyester resin. Item 3. The water purification filter according to Item 1, wherein the aliphatic polyester resin is polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, polyethylene terephthalate succinate, or 3-hydroxybutyrate-co-3-hydroxyhexanoate polymer. Item 4. The water purification filter according to any one of Items 1 to 3, wherein the water purification filter has a cylindrical shape. Effect of the Invention
[0015] According to the water purification filter of the present invention, by being provided with the configuration of the present invention, a water purification filter containing activated carbon as a filter material and a biodegradable polymer as a binder component, in which the activated carbon is fused to each other by the biodegradable polymer, can maintain a certain level of free residual chlorine filtration capacity, have a filtration flow rate that is practically problem-free even when used as a pot-type water purifier, and have a certain degree of high hardness and excellent handleability. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic perspective view illustrating an example of a water purification filter in which a nonwoven fabric sheet is formed in a wound state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The water purification filter of the present invention is a water purification filter comprising activated carbon and a biodegradable polyester resin, and wherein the activated carbon is fused to itself by the biodegradable polyester resin, the activated carbon is in the form of fiber, the biodegradable polyester resin has a melting point of 80 to 140°C and is contained as a sheath of a core-sheath type composite fiber, and the difference between the melting point of the synthetic resin contained as the core of the core-sheath type composite fiber and the melting point of the biodegradable polyester resin (the melting point of the synthetic resin contained as the core - the melting point of the biodegradable polyester resin) is 20°C or more, the water purification filter is formed by winding a nonwoven fabric sheet containing the fibrous activated carbon and the core-sheath type composite fiber, and the density of the water purification filter is 0.12 to 0.30 g / cm. 3 The specific surface area of the water purification filter is 500 to 1800 m 2 The materials constituting the water purification filter of the present invention will be described in detail below.
[0018] <Activated carbon> The water purification filter of the present invention contains fibrous activated carbon. Since the biodegradable polyester resin, which is a binder component, itself has a relatively hard and brittle property, the obtained water purification filter may have poor mechanical strength and poor handleability. However, according to the water purification filter of the present invention, the activated carbon itself is fibrous, which makes it easier to improve the brittleness caused by the biodegradable polyester resin, and the water purification filter has excellent handleability.
[0019] The specific surface area of the fibrous activated carbon contained in the water purification filter of the present invention is set to 600 to 3000 m from the viewpoint of increasing the strength of the water purification filter while making it easy to set the specific surface area of the water purification filter of the present invention described later. 2 / g, and 1000 to 2000m 2 In addition to the above viewpoints, from the viewpoint of further suppressing the generation of coal dust during the initial use of the water purification filter of the present invention, it is more preferable that the molecular weight is 1100 to 1500 m 2 / g is particularly preferable. In the present invention, the specific surface area is a value calculated based on the nitrogen adsorption isotherm at 77.4K. Specifically, the nitrogen adsorption isotherm is created as follows. The sample to be measured is cooled to 77.4K (the boiling point of nitrogen), nitrogen gas is introduced, and the adsorption amount V [cc / g] of the nitrogen gas is measured by the volumetric method. At this time, the pressure P [hPa] of the introduced nitrogen gas is gradually increased, and the value divided by the saturated vapor pressure P0 [hPa] of the nitrogen gas is set as the relative pressure P / P0, and the adsorption amount for each relative pressure is plotted to create a nitrogen adsorption isotherm. The adsorption amount of nitrogen gas can be measured using a commercially available automatic gas adsorption amount measuring device (for example, the product name "AUTOSORB-1-MP" (manufactured by QUANTCHROME), etc.). In the present invention, the specific surface area is calculated according to the BET method based on the nitrogen adsorption isotherm. This analysis can be performed using known means such as an analysis program attached to the above device.
[0020] The average fiber diameter of the fibrous activated carbon contained in the water purification filter of the present invention is preferably 5 to 30 μm, more preferably 10 to 25 μm. By setting the average fiber diameter in this range, it becomes easier to achieve both free residual chlorine filtration capacity and filtration flow rate. In the present invention, the average fiber diameter of the fibrous activated carbon is calculated by measuring with a reflecting microscope in accordance with JIS K 1477:2007 7.3.1.
[0021] Furthermore, the water purification filter of the present invention can contain activated carbon other than fibrous activated carbon, for example, granular activated carbon, as long as the effects of the present invention are achieved.
[0022] In the water purification filter of the present invention, the content (mass%) of activated carbon including fibrous activated carbon is not particularly limited, but may be, for example, 50 to 90 mass%. In particular, from the viewpoint of suppressing the generation of coal dust during the initial use of the water purification filter of the present invention while maintaining a certain free residual chlorine filtering ability and filtration flow rate, and increasing the density of the water purification filter to improve the handleability as a filter, the content is preferably 50 to 70 mass%, and particularly preferably 55 to 65 mass%.
[0023] Specifically, fibers containing a biodegradable polyester resin as a binder component, which will be described later, have a higher affinity for water and a higher thermal shrinkage rate than fibers containing copolymerized polyethylene terephthalate or polyolefin as a binder component. The present inventors have found that an activated carbon filter containing fibers containing a biodegradable polyester resin as a binder component undergoes relatively large thermal shrinkage when the biodegradable polyester resin is thermally melted to form a filter, and has a filter density somewhat higher than that of an activated carbon filter containing fibers containing copolymerized polyethylene terephthalate or polyolefin as a binder component. By setting the content of activated carbon to 50 to 70 mass%, particularly preferably 55 to 65 mass%, it is possible to increase the content of the biodegradable polyester resin, which will be described later, and as a result, the affinity of the obtained filter for water (water compatibility) is increased, and while maintaining a constant filtration flow rate, the filter density can be relatively increased, thereby increasing the filter hardness and improving the handleability. In addition, by setting the content of activated carbon at 50 to 70 mass %, particularly preferably 55 to 65 mass %, it becomes easier to suppress the generation of coal dust during the initial use of the filter.
[0024] <Biodegradable polyester resin contained as the sheath of a core-sheath type composite fiber, and said core-sheath type composite fiber> The water purification filter of the present invention contains a biodegradable polyester resin as a binder component. The biodegradable polyester resin has a melting point of 80 to 140°C and is contained as a sheath of a core-sheath type composite fiber, and fuses the activated carbon together when at least a part of the sheath is softened or melted and solidified. The difference between the melting point of the synthetic resin contained as the core of the core-sheath type composite fiber and the melting point of the biodegradable polyester resin (melting point of the synthetic resin contained as the core - melting point of the biodegradable polyester resin) is 20°C or more.
[0025] In the present invention, biodegradability refers to the property of a substance being decomposed by microorganisms; specifically, it refers to the property of promoting hydrolysis when the substance is placed in an environment with appropriate moisture and temperature, such as in compost or soil, and then allowing decomposition by microorganisms to proceed, ultimately resulting in carbon dioxide and water that can be circulated back into nature.
[0026] More preferred biodegradability of the biodegradable polyester resin of the present invention is one in which the degree of biodegradation measured in accordance with JIS K 6953-1:2011 is 60% or more within 180 days.
[0027] In addition, a more preferred example of biodegradability that the biodegradable polyester resin of the present invention has is one in which at least 60% by mass of the organic carbon in the biodegradable polyester resin is converted to carbon dioxide within 180 days under active decomposition conditions in accordance with the method of DIN EN ISO 14855-1:2012.
[0028] The biodegradable polyester resin contained in the sheath of the core-sheath type composite fiber constituting the water purification filter of the present invention is preferably an aliphatic polyester resin. As the aliphatic polyester resin, polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, polyethylene terephthalate succinate, or 3-hydroxybutyrate-co-3-hydroxyhexanoate polymer is preferable. Among them, from the viewpoint of improving the water permeability of the water purification filter by improving the affinity for water while improving the bonding with the synthetic resin contained as the core of the core-sheath type composite fiber described later, it is more preferable that the aliphatic polyester resin is polylactic acid or polybutylene succinate.
[0029] The melting point of the biodegradable polyester resin is from 80 to 140°C, preferably from 100 to 140°C, and more preferably from 110 to 140°C.
[0030] When the biodegradable polyester resin contained in the sheath of the core-sheath type composite fiber constituting the water purification filter of the present invention is polylactic acid, the polylactic acid is a copolymer of D-lactic acid and L-lactic acid, and has a melting point of 110 to 140°C.
[0031] As the lactic acid monomer constituting polylactic acid, there are optical isomers of D-form (D-lactic acid) and L-form (L-lactic acid). For example, when about 3 mol% of the D form is copolymerized with the L form, the melting point is about 150°C, when about 7 mol% of the D form is copolymerized, the melting point is about 140°C, and when about 12 mol% of the D form is copolymerized, the melting point is about 110°C, and the melting point of polylactic acid can be controlled. According to the study by the present inventors, by making polylactic acid a copolymer of D-lactic acid and L-lactic acid and adjusting the copolymerization ratio of the D form and the L form to have a melting point of 110°C or more and 140°C or less, it is possible to obtain a more appropriate fluidity when melted in a heat treatment for bonding the fibrous activated carbons together, while maintaining the pores of the fibrous activated carbon (the pores are not filled up too much with the binder component), and it is easier to suppress the thermal deformation of the core of the core-sheath type composite fiber in the heat treatment. In the present invention, the melting point is measured using a DSC (differential scanning calorimeter) at a DSC temperature rise rate of 20° C. / min, and the temperature giving an extreme value in the obtained melting endothermic curve is taken as the melting point.
[0032] When polylactic acid is contained as the sheath of the core-sheath composite fiber, the content of D-lactic acid in the polylactic acid is preferably 7 to 12 mol%. In the present invention, the content of D-lactic acid in polylactic acid is measured by weighing 0.3 g of polylactic acid, adding it to 6 mL of 1N potassium hydroxide / methanol solution, and thoroughly stirring at 65°C. Then, 450 μL of sulfuric acid is added and stirred at 65°C to decompose the polylactic acid, and 5 mL is measured as a sample. This sample is mixed with 3 mL of pure water and 13 mL of methylene chloride, shaken, and allowed to stand for separation, and about 1.5 mL of the organic layer at the bottom is collected and filtered with a 0.45 μm pore size HPLC disk filter, and then gas chromatographic measurement is performed using a Hewlet Packard HP-6890 Series GC system. The ratio (%) of the peak area of D-lactic acid methyl ester to the total peak area of lactate methyl ester is calculated, and this is the D-lactic acid content (mol%) of polylactic acid.
[0033] In the water purification filter of the present invention, the biodegradable polyester resin contained as the sheath of the core-sheath type composite fiber may have a melt flow rate (MFR) of 5 to 20 g / 10 min. In the present invention, the MFR is measured in accordance with JIS K7210 under conditions of a test temperature of 190° C. and a load of 2.16 kg.
[0034] In the water purification filter of the present invention, the synthetic resin contained as the core of the core-sheath type composite fiber has a melting point difference between the synthetic resin and the biodegradable polyester resin contained as the sheath (melting point of the synthetic resin contained as the core-melting point of the biodegradable polyester resin contained as the sheath) of 20°C or more, preferably 30°C or more. In the water purification filter of the present invention, the synthetic resin contained as the core of the core-sheath type composite fiber is not particularly limited as long as the melting point difference between the synthetic resin and the biodegradable polyester resin contained as the sheath (melting point of the synthetic resin contained as the core-biodegradable polyester resin contained as the sheath) is 20°C or more. Examples of synthetic resins contained as the core of the core-sheath type composite fiber include polyester and polyamide. Among them, from the viewpoint of further improving the biodegradability of the water purification filter of the present invention, suppressing the thermal deformation of the core of the core-sheath type composite fiber in the heat treatment when bonding the fibrous activated carbon, and increasing the filter density, it is preferable that the synthetic resin contained as the core of the core-sheath type composite fiber is a biodegradable polyester resin having a melting point of 150°C or more and 200°C or less. Examples of the biodegradable polyester resin include aliphatic polyesters, and examples of the aliphatic polyester resins preferably include polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, polyethylene terephthalate succinate, or 3-hydroxybutyrate-co-3-hydroxyhexanoate polymer. Among them, it is preferable to use polylactic acid, which is a copolymer of D-lactic acid and L-lactic acid and has a melting point of 150°C or more and 190°C or less. In this case, the D-form content in the polylactic acid contained as the core portion is 0.5 to 2 mol%, preferably 1 to 2 mol%. From the viewpoint of further suppressing thermal deformation of the core portion of the core-sheath type composite fiber in the heat treatment for bonding the fibrous activated carbon, the glass transition point of the synthetic resin contained as the core portion is preferably 50°C or higher and 65°C or lower. In the present invention, the glass transition point is measured using a DSC (differential scanning calorimeter) at a temperature rise rate of 20°C / min, and the intermediate value between the temperatures of two bending points resulting from the glass transition in the obtained temperature rise curve is determined, and this is defined as the glass transition point.
[0035] In the present invention, the mass ratio of the core to the sheath of the core-sheath type composite fiber (core / sheath) is not particularly limited, but is preferably 3 / 7 to 7 / 3, and more preferably 4 / 6 to 6 / 4. In the present invention, the fineness of the core-sheath type composite fiber is not particularly limited, but is preferably 1 to 5 dtex, and more preferably 1 to 3 dtex. In addition, the average fiber length is not particularly limited, but is preferably 10 to 100 mm, and more preferably 30 to 70 mm.
[0036] In the water purification filter of the present invention, the cross-sectional shape of the core-sheath type composite fiber is not particularly limited, but a circular shape is preferable.
[0037] In the water purification filter of the present invention, the content (mass%) of the core-sheath type composite fiber is not particularly limited, and may be, for example, 10 to 50 mass%. In particular, from the viewpoint of suppressing the generation of coal dust during the initial use of the water purification filter of the present invention while maintaining a certain free residual chlorine filtration capacity and filtration flow rate, and increasing the density of the water purification filter to improve the handleability as a filter, the content is preferably 30 to 50 mass%, and particularly preferably 35 to 45 mass%.
[0038] <Water purification filter> The water purification filter of the present invention is formed by winding a nonwoven fabric sheet containing the above-mentioned fibrous activated carbon and the above-mentioned core-sheath type composite fiber (a core-sheath type composite fiber containing a biodegradable polyester resin having a melting point of 80 to 140°C as a sheath and a synthetic resin having a melting point 20°C higher than the melting point of the biodegradable polyester resin as a core). FIG. 1 is a schematic perspective view illustrating an example of a water purification filter 1 molded in a wound state of a nonwoven fabric sheet 2. In FIG. 1, the water purification filter 1 is molded in a wound state of a nonwoven fabric sheet 2, and the water purification filter 1 is arranged so that the longitudinal direction of the nonwoven fabric sheet 2 is perpendicular to the height direction of the water purification filter 1 (the vertical direction of the paper). In FIG. 1, the water purification filter 1 has a surface or back surface of the nonwoven fabric sheet 2 that forms the side surface 12 of the water purification filter 1, and the longitudinal ends (ears) of the nonwoven fabric sheet 2 are arranged in a spiral shape to form the upper surface 13 and the lower surface (not shown) of the water purification filter 1. FIG. 1 shows an example of a cylindrical water purification filter having a space portion 3 that communicates in the height direction at the center of the water purification filter 1. It is preferable that the water to be purified is passed in the radial direction of the water purification filter 1. In this way, the longitudinal ends of the nonwoven fabric sheet 2 are arranged in multiple layers to form the upper surface 13 and the lower surface of the water purification filter 1, and the hardness of the upper surface 13 and the lower surface can be increased and the handleability can be improved in terms of density, which will be described later. In addition, by rolling the nonwoven fabric sheet 2 under tension, the water purification filter 1 can be compressed in the radial direction from the side surface 12 toward the center, and the hardness of the side surface 12 can be increased and the handleability can be improved. Examples of a method for manufacturing the water purification filter include preparing a nonwoven fabric sheet 2, winding the nonwoven fabric sheet 2 under tension, for example, around a thin resin core, fixing the shape by heat treatment or the like, removing the core, and cutting the water purification filter 1, as necessary, in a plane direction perpendicular to the height direction so that the water purification filter 1 has a predetermined height, to obtain the water purification filter 1.
[0039] The water purification filter of the present invention has a density of 0.12 to 0.30 g / cm 3By setting the density in this range, it is possible to maintain a certain free residual chlorine filtering capacity while providing a filtering flow rate suitable for a pot-type water purifier. From the viewpoint of achieving both a high filtering flow rate and an excellent handling property by increasing hardness, the density is set to 0.14 to 0.25 g / cm. 3 is preferable, and 0.140 to 0.175 g / cm 3 In the present invention, the density of the water purification filter is determined by drying the water purification filter in a hot air dryer at 80° C. for 3 hours, cooling it to room temperature in a desiccator, weighing the filter, and multiplying the weight (g) by the volume (cm) of the water purification filter. 3 ) The density can be adjusted by adjusting the weight and thickness of the nonwoven fabric sheet to be wound, or by adjusting the tension when winding. It can also be adjusted by the form of the nonwoven fabric sheet, which will be described later. Specifically, the form of the nonwoven fabric sheet can be broadly classified into dry nonwoven fabrics such as needle punched nonwoven fabrics and wet nonwoven fabrics such as wet papermaking nonwoven fabrics, and dry nonwoven fabrics have longer fiber length and are bulkier than wet nonwoven fabrics, resulting in a lower density. Therefore, for example, when a fiber containing polylactic acid is used as a binder component, while using the other adjustment methods described above, the density of the dry nonwoven fabric can be adjusted to 0.12 to 0.20 g / cm. 3 For wet nonwoven fabrics, it is 0.20 to 0.40 g / cm 3 It can be adjusted within a certain range.
[0040] The water purification filter of the present invention has a specific surface area of 500 to 1800 m 2 / g. By setting the specific surface area in this range, it is possible to ensure the ease of handling of the activated carbon filter while maintaining a certain level of free residual chlorine filtering ability. In particular, from the viewpoint of suppressing the generation of coal dust during the initial use of the water purification filter of the present invention while maintaining a certain level of free residual chlorine filtering ability and filtration flow rate, and increasing the density of the water purification filter to improve the ease of handling as a filter, it is preferable to set the specific surface area to 650 to 800 m. 2 / g is preferred, and 700 to 775m 2The specific surface area can be adjusted by adjusting the specific surface area and content of the fibrous activated carbon, the content of the biodegradable polyester resin disposed in the sheath of the core-sheath type composite fiber, and the heat treatment conditions when bonding the fibrous activated carbon.
[0041] Regarding the hardness of the water purification filter of the present invention, the average value of the hardness of the upper surface 13 and the lower surface is preferably 10 to 75, more preferably 30 to 70, and even more preferably 30 to 50, from the viewpoint of reducing cracks and chips of the water purification filter, improving the handling property, and improving the filtration flow rate, and the average value of the hardness of the side surface 12 of the water purification filter is preferably 20 to 90, more preferably 40 to 60, and even more preferably 40 to 50, from the viewpoint of reducing cracks and chips of the water purification filter, improving the handling property, and improving the filtration flow rate, and the average value of the hardness is measured using a durometer model GS-701N manufactured by Techrock Co., Ltd. in accordance with JIS S 6050, and the hardness of the upper surface 13 in the height direction of the water purification filter is measured by placing the water purification filter in the center of a hollow base so that the upper surface 13 faces upward as shown in FIG. 1, fixing it so that it does not move, measuring three points on the upper surface 13, and reading the median value. For the hardness of the bottom surface, the water purification filter is placed in the center of a hollow base with the bottom surface facing up, fixed so as not to move, and measurements are taken at three points on the bottom surface. The average of the hardnesses at the three points on the top surface and the three points on the bottom surface is taken as the average hardness of the top surface 13 and the bottom surface. For the hardness of the side surface 12 of the water purification filter, the water purification filter is placed in the center of a hollow base with the top surface 13 facing up as shown in Figure 1, fixed so as not to move, and the hardness meter is pressed horizontally against the filter to measure the three points on the side surface 12, and the median value is read.
[0042] The height of the water purification filter can be 10 to 250 mm. The volume of the water purification filter can be 1 to 500 cm. 3 Examples include:
[0043] The nonwoven fabric sheet constituting the water purification filter contains the above-mentioned fibrous activated carbon and the above-mentioned core-sheath type composite fiber containing the biodegradable polyester resin as a sheath. The basis weight of the sheet is 10 to 100 g / m 2 The form of the nonwoven fabric sheet is not particularly limited as long as it contains the above-mentioned fibrous activated carbon and core-sheath type composite fiber, but is preferably a dry nonwoven fabric, and more preferably a needle punch nonwoven fabric. Dry nonwoven fabrics tend to have a lower density than wet papermaking nonwoven fabrics, for example, and are suitable for producing a water purification filter having the above-mentioned density.
[0044] <Uses of the water purification filter of the present invention> The water purification filter of the present invention is used as a filter for a pot-type (pitcher-type) water purifier in which raw water stored in a storage section (reservoir tank) is allowed to fall under its own weight and pass through the filter for purification. In particular, as illustrated in Fig. 1, it is preferable that the water purification filter is cylindrical, the water purification filter is arranged so that the axial direction of the cylinder (the vertical direction in Fig. 1) is the vertical direction, and the water to be purified is passed through the water purification filter 1 in the radial direction (i.e., (1) the raw water that flows into the space section 3 passes through the water purification filter in the radial direction and flows out from the side surface 12 side, or (2) the raw water that flows in from the side surface 12 side passes through the water purification filter in the radial direction and flows out from the space section 3). EXAMPLES
[0045] The present invention will be described in detail below with reference to examples, although the present invention is not limited to these examples.
[0046] <Example 1> The fibrous activated carbon used was A-10 (specific surface area 1300 m) manufactured by Unitika Ltd. 2A core-sheath type composite fiber (fineness 2.2 dtex, average fiber length 51 mm) was prepared, in which the core was composed of polylactic acid (melting point 170°C, glass transition point 57°C) which was a copolymer of D-lactic acid and L-lactic acid (D-form content 1.4 mol%) and the sheath was composed of polylactic acid (melting point 130°C, melt flow rate 10 g / 10 mm) which was a copolymer of D-lactic acid and L-lactic acid (D-form content 10 mol%), the mass ratio of the core to the sheath (core / sheath) was 5 / 5, and the cross section was circular.
[0047] 60 parts by mass of the prepared fibrous activated carbon and 40 parts by mass of the prepared core-sheath type composite fiber were mixed and carded to form a thin web, which was then needle-punched, heat-treated at an atmospheric temperature of 90°C, and cooled to obtain a needle-punched nonwoven fabric A. The basis weight of the nonwoven fabric was 65 g / m 2 , the thickness was 0.50 mm.
[0048] A cylindrical iron pipe having an outer diameter of 27.6 mm was prepared as a core, and the needle-punched nonwoven fabric A obtained above was wound around the core to a predetermined outer diameter. The wound needle-punched nonwoven fabric A was then placed in a furnace and heat-treated at an atmospheric temperature of 130° C. for 1 hour, and then naturally cooled. The core was then removed, and the nonwoven fabric was cut to a length of 82 mm with a cutter to obtain a cylindrical water purification filter of the present invention. The height of the water purification filter was 82 mm, the outer diameter was 38.5 mm, and the inner diameter was 27.6 mm. In the obtained water purification filter, the fibrous activated carbons were fused and fixed to each other in a state in which a part of the polylactic acid arranged in the sheath of the core-sheath type composite fiber was melted and solidified. The core of the core-sheath type composite fiber was hardly deformed by heat.
[0049] <Example 2> A cylindrical iron pipe having an outer diameter of 27.6 mm was prepared as a winding core, and the same needle-punched nonwoven fabric A as in Example 1 was wound around the winding core to a predetermined outer diameter. The wound needle-punched nonwoven fabric A was then placed in a furnace and heat-treated at an atmospheric temperature of 150° C. for 1 hour, and then naturally cooled. The winding core was then removed, and the nonwoven fabric was cut to a length of 82 mm with a cutter to obtain a cylindrical water purification filter of the present invention. The height of the water purification filter was 82 mm, the outer diameter was 38.5 mm, and the inner diameter was 27.6 mm. In the obtained water purification filter, the fibrous activated carbons were fused and fixed to each other in a state in which most of the polylactic acid arranged in the sheath of the core-sheath type composite fiber was melted and solidified. The core of the core-sheath type composite fiber was slightly thermally deformed.
[0050] <Example 3> The fibrous activated carbon used was A-15 (specific surface area 1700 m) manufactured by Unitika Ltd. 2 A core-sheath type composite fiber (fineness 2.2 dtex, average fiber length 51 mm) was prepared, in which the core was composed of polylactic acid (melting point 170°C, glass transition point 57°C) which was a copolymer of D-lactic acid and L-lactic acid (D-form content 1.4 mol%) and the sheath was composed of polylactic acid (melting point 130°C, melt flow rate 10 g / 10 mm) which was a copolymer of D-lactic acid and L-lactic acid (D-form content 10 mol%), the mass ratio of the core to the sheath (core / sheath) was 5 / 5, and the cross section was circular.
[0051] 80 parts by mass of the prepared fibrous activated carbon and 20 parts by mass of the prepared core-sheath type composite fiber were mixed and carded to form a thin web, which was then needle-punched, heat-treated at an atmospheric temperature of 90°C, and cooled to obtain a needle-punched nonwoven fabric B. The basis weight of the nonwoven fabric was 65 g / m 2 , the thickness was 0.52 mm.
[0052] A cylindrical iron pipe having an outer diameter of 27.6 mm was prepared as a core, and the needle-punched nonwoven fabric B obtained above was wound around the core to a predetermined outer diameter. The wound needle-punched nonwoven fabric B was then placed in a furnace and heat-treated at an atmospheric temperature of 130° C. for 1 hour, and then naturally cooled. The core was then removed, and the nonwoven fabric was cut to a length of 82 mm with a cutter to obtain a cylindrical water purification filter of the present invention. The height of the water purification filter was 82 mm, the outer diameter was 38.5 mm, and the inner diameter was 27.6 mm. In the obtained water purification filter, the fibrous activated carbons were fused and fixed to each other in a state in which a part of the polylactic acid arranged in the sheath of the core-sheath type composite fiber was melted and solidified. The core of the core-sheath type composite fiber was hardly deformed by heat.
[0053] <Example 4> The fibrous activated carbon used was A-10 (specific surface area 1300 m) manufactured by Unitika Ltd. 2 The core-sheath composite fiber was prepared as follows: polylactic acid (melting point 170°C, glass transition point 57°C), which is a copolymer of D-lactic acid and L-lactic acid (D-form content 1.4 mol%) as a core, polybutylene succinate (melting point 120°C, melt flow rate 15 g / 10 mm) as a sheath, the mass ratio of the core to the sheath (core / sheath) was 5 / 5, and the cross section was circular (fineness 2.2 dtex, average fiber length 51 mm).
[0054] 60 parts by mass of the prepared fibrous activated carbon and 40 parts by mass of the prepared core-sheath type composite fiber were mixed and carded to form a thin web, which was then needle-punched, heat-treated at an atmospheric temperature of 90°C, and cooled to obtain a needle-punched nonwoven fabric C. The basis weight of the nonwoven fabric was 66 / m 2 , the thickness was 0.55 mm.
[0055] A cylindrical iron pipe having an outer diameter of 27.6 mm was prepared as a winding core, and the needle-punched nonwoven fabric C obtained above was wound around the winding core to a predetermined outer diameter. The wound needle-punched nonwoven fabric C was then placed in a furnace and heat-treated at an atmospheric temperature of 130° C. for 1 hour, and then naturally cooled. The winding core was then removed, and the fabric was cut to a length of 82 mm with a cutter to obtain a cylindrical water purification filter of the present invention. The height of the water purification filter was 82 mm, the outer diameter was 38.5 mm, and the inner diameter was 27.6 mm. In the obtained water purification filter, the fibrous activated carbons were fused and fixed to each other in a state in which a part of the polybutylene succinate arranged in the sheath of the core-sheath type composite fiber was melted and solidified. The core of the core-sheath type composite fiber was hardly deformed by heat.
[0056] <Example 5> A cylindrical iron pipe having an outer diameter of 27.6 mm was prepared as a winding core, and the same needle-punched nonwoven fabric C as in Example 4 was wound around the winding core to a predetermined outer diameter. The wound needle-punched nonwoven fabric C was then placed in a furnace and heat-treated at an atmospheric temperature of 150° C. for 1 hour, and then naturally cooled. The winding core was then removed, and the nonwoven fabric was cut to a length of 82 mm with a cutter to obtain a cylindrical water purification filter of the present invention. The height of the water purification filter was 82 mm, the outer diameter was 38.5 mm, and the inner diameter was 27.6 mm. In the obtained water purification filter, the fibrous activated carbons were fused and fixed to each other in a state in which most of the polybutylene succinate arranged in the sheath of the core-sheath type composite fiber was melted and solidified. The core of the core-sheath type composite fiber was slightly thermally deformed.
[0057] <Measurement of physical properties, etc.> 1. Specific surface area and average fiber diameter of fibrous activated carbon Measurements were carried out using the methods described above. 2.Melting point of biodegradable polyester resin Measurement was performed using a DSC (differential scanning calorimeter) at a DSC temperature rise rate of 20° C. / min, and the temperature at which the extreme value was obtained in the obtained melting endothermic curve was taken as the melting point. 3. Content of D-lactic acid in polylactic acid Measurements were carried out using the methods described above. 4. Melt flow rate of biodegradable polyester resin in the sheath Measurements were carried out using the methods described above. 5. Glass transition temperature of biodegradable polyester resin in the core Measurements were performed using a DSC (differential scanning calorimeter) at a temperature rise rate of 20°C / min. The intermediate temperature between the two inflection points resulting from the glass transition in the obtained temperature rise curve was determined, and this was regarded as the glass transition point. 6. Density, specific surface area and hardness of water purification filters Measurements were carried out using the methods described above. 7. Free residual chlorine filtration capacity of water purification filters The free residual chlorine filtration capacity was measured using a continuous water purifier in accordance with JIS S 3201 2019 6.5.2. The filtration flow rate was 1.2 L / min. 8. Filtration flow rate 8-1.Preparing the cartridge The filters of Examples 1 to 4 were loaded into a cartridge case (ZR-003-B-4 manufactured by ZeroWater) and immersed in water for 20 minutes. 8-2. Filtration flow rate measurement 1) Place the cartridge in the reservoir tank and fill it with water until it is full. 2) After the reservoir tank is empty, fill it up with water again. 3) Repeat step 2) two more times. 4) The filter was filled to the top with water again, and the amount of filtered water coming out in one minute was measured and this was taken as the filtration flow rate. 9. Evaluation of coal dust amount during initial use of water purification filter 9-1.Preparing the cartridge The cartridge was prepared in the same manner as in 8-1. 9-2. Evaluation of coal dust volume 1) Attach the cartridge to the reservoir tank and fill it with water until it is full. 2) 0.5 L of the filtered water was collected and filtered using a white membrane filter (pore size 0.45 μm), and the amount of coal dust remaining on the membrane filter was evaluated according to the following criteria. A lot: The presence of coal dust is clearly visible to the naked eye. Little: Coal dust can be confirmed by close visual inspection. Very little: No coal dust can be seen with the naked eye. 10. Evaluation of ease of use Five panelists replaced the water purification filters and evaluated whether there were any practical problems using the following criteria. ⊚: 5 out of 5 people evaluated that it was not problematic in practical use, and 0 people evaluated that it was problematic in practical use. ○: Four out of five people evaluated that it was not problematic in practical use, and one person evaluated that it was problematic in practical use. △: Three out of five people evaluated that there was no practical problem, and two people evaluated that there was a practical problem. ×: Three or more out of five people evaluated that there was a problem in practical use.
[0058] The results of each example are shown in Table 1.
[0059] [Table 1]
[0060] The water purification filters of Examples 1 to 5 are water purification filters comprising activated carbon and a biodegradable polyester resin, and wherein the activated carbon is fused to each other by the biodegradable polyester resin, the activated carbon is in the form of a fiber, the biodegradable polyester resin has a melting point of 80 to 140°C and is contained as a sheath of a core-sheath type composite fiber, and the difference between the melting point of the synthetic resin contained as the core of the core-sheath type composite fiber and the melting point of the biodegradable polyester resin (the melting point of the synthetic resin contained as the core - the melting point of the biodegradable polyester resin) is 20°C or more, the water purification filter is formed by winding a nonwoven fabric sheet containing the fibrous activated carbon and the core-sheath type composite fiber, and the density of the water purification filter is 0.12 to 0.30 g / cm 3 The specific surface area of the water purification filter is 500 to 1800 m 2 / g, a water purification filter containing activated carbon as a filter medium and a biodegradable polymer as a binder component, with activated carbon particles fused together by the biodegradable polymer, maintained a certain level of free residual chlorine filtration capacity, had a filtration flow rate that was practically problem-free even when used as a pot-type water purifier, and had a certain degree of high hardness and was easy to handle.
[0061] Among them, the water purification filters of Examples 1, 2, 4 and 5 have the above-mentioned configuration and a density of 0.14 to 0.25 g / cm 3 Therefore, while maintaining the filtration flow rate, the hardness was increased and the handling was excellent. In addition, the generation of coal dust during the initial use of the water purification filter was further suppressed.
[0062] In particular, the water purification filters of Examples 1 and 4 had the above-mentioned configuration and the hardness of the upper and lower surfaces was 30 to 50, and therefore had better free residual chlorine filtration capacity and filtration flow rate than Examples 2 and 5. [Explanation of symbols]
[0063] 1. Water filter 2 Non-woven fabric sheet 3 Space section 12 Side of the water filter 13 Top of water filter
Claims
1. A water purification filter comprising activated carbon and a biodegradable polyester resin, the activated carbon being fused together by the biodegradable polyester resin, The activated carbon is in the form of fiber, The biodegradable polyester resin has a melting point of 80 to 140° C. and is contained as a sheath of a core-sheath type composite fiber, the difference between the melting point of the synthetic resin contained as the core of the sheath-core type composite fiber and the melting point of the biodegradable polyester resin (the melting point of the synthetic resin contained as the core - the melting point of the biodegradable polyester resin) is 20°C or more, the biodegradable polyester resin is polybutylene succinate, and the synthetic resin contained as the core of the core-sheath type composite fiber is polylactic acid; the water purification filter is formed by winding a nonwoven fabric sheet containing the fibrous activated carbon and the core-sheath type composite fiber, The density of the water purification filter is 0.12 to 0.30 g / cm 3 and The specific surface area of the water purification filter is 500 to 1800 m 2 / g water purification filter.
2. A water purification filter comprising activated carbon and a biodegradable polyester resin, the activated carbon being fused to each other by the biodegradable polyester resin, The activated carbon is in the form of fiber, The biodegradable polyester resin has a melting point of 80 to 140° C. and is contained as a sheath of a core-sheath type composite fiber, the difference between the melting point of the synthetic resin contained as the core of the sheath-core type composite fiber and the melting point of the biodegradable polyester resin (the melting point of the synthetic resin contained as the core - the melting point of the biodegradable polyester resin) is 20°C or more, the water purification filter is formed by winding a nonwoven fabric sheet containing the fibrous activated carbon and the core-sheath type composite fiber, The density of the water purification filter is 0.12 to 0.30 g / cm 3 ; A water purification filter (excluding those containing activated carbon other than fibrous activated carbon), wherein the specific surface area of the water purification filter is 500 to 1800 m 2 / g.
3. The water purification filter according to claim 2 , wherein the biodegradable polyester resin is an aliphatic polyester resin.
4. The water purification filter according to claim 2, wherein the aliphatic polyester resin is polylactic acid, polyethylene succinate, polybutylene succinate, polybutylene succinate adipate, polybutylene adipate terephthalate, polyethylene terephthalate succinate, or 3-hydroxybutyrate-co-3-hydroxyhexanoate polymer.
5. The water purification filter according to any one of claims 1 to 4, wherein the water purification filter has a cylindrical shape.
Citation Information
Patent Citations
Columnar adsorbent and production thereof
JP1992281805A
Water treating filter material
JP1996052347A
Antibacterial sheet of active carbon and antibacterial deodorant covering material for wound
JP2001333973A
Filter bag for drink
JP2002177148A
Filter device and method using same
JP2004504126A